Barrio dreams : Puerto Ricans, Latinos, and the neoliberal city - Dávila, Arlene M., 1965- (University of California Press, 2004)
Arlene Davila brilliantly considers the cultural politics of urban space in this lively exploration of Puerto Rican and Latino experience in New York, the global center of culture and consumption, where Latinos are now the biggest minority group. Analyzing the simultaneous gentrification and Latinization of what is known as El Barrio or Spanish Harlem, Barrio Dreams makes a compelling case that--despite neoliberalism's race-and ethnicity-free tenets--dreams of economic empowerment are never devoid of distinct racial and ethnic considerations.